2021
DOI: 10.1111/ajt.16490
|View full text |Cite
|
Sign up to set email alerts
|

Donor genetic variants as risk factors for thrombosis after liver transplantation: A genome-wide association study

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…In the largest genetic study of liver transplant donors to date involving 775 adult donors and 310 pediatric donors, there was no association between known thrombophilic gene loci and post-transplant thrombosis. This study identified three previously unrecognized genes, AK4 , RGS5 , and ETFA , as being associated with increased risk of post-transplant thrombosis and graft loss, and patient mortality was higher in patients with post-transplant thrombosis 17 …”
Section: Thrombophiliasmentioning
confidence: 83%
See 2 more Smart Citations
“…In the largest genetic study of liver transplant donors to date involving 775 adult donors and 310 pediatric donors, there was no association between known thrombophilic gene loci and post-transplant thrombosis. This study identified three previously unrecognized genes, AK4 , RGS5 , and ETFA , as being associated with increased risk of post-transplant thrombosis and graft loss, and patient mortality was higher in patients with post-transplant thrombosis 17 …”
Section: Thrombophiliasmentioning
confidence: 83%
“…Outcome of the recipient will depend on the phenotype of the donor rather than the presence of a particular mutation Difficult to speculate the outcome due to difficulties in variant interpretation, heterogenous phenotype among different variants, and incomplete knowledge due to under-reporting of clinical data Li et al [17] single unprovoked thrombotic event, the transplant team could consider using the liver for transplantation.…”
Section: Genetic Diagnosis On Multigene Panel Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 2 candidate risk loci ( AK4 and RGS5 ) but also found that previously associated thrombophilia risk loci in donors did not increase the thrombosis risk in liver transplant recipients. 44 Another study assessed 4 separate genetic matching scores, which were utilized to calculate differences between transplant donors and recipients, for liver transplant outcomes with robust statistical power. This study showed joint testing could help with detecting SNPs significantly associated with acute rejection in liver transplantation.…”
Section: Genome-wide Association Studies In Solid Organ Transplantationmentioning
confidence: 99%